Evaluation of Neutrophil Percentage to Albumin Ratio as Predictor of Mortality in Patients with Covid-19 - Haseeb U Rehman, Rizwana Salik Nukrich, Muhammad Azhar Ahmed, Syed Muhammad Umair Dilawar, Elisha Shalim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inflammatory acute respiratory syndrome (SARS) is caused by the COV-2 virus. Neutrophils have been implicated in the pathophysiology of the COVID-19 pandemic since its inception, particularly in individuals with advanced disease. This is confirmed by a large number of studies. Methods: The study included 200 patients, of whom 100 were in the critical group (group 1) and 100 were in the non-critical group (group 2). White blood cell (WBC) percentage, neutrophil count, albumin, and demographic information were recorded. Neutrophil percentage x 100 /Albumin (g/dl) was used to construct the neutrophil count to albumin ratio (NPAR). To determine whether the measure may be utilized as a predictor for mortality, the NPAR is then compared between groups 1 and 2, as well as between discharge and mortality groups. Results: Age and gender had no statistically significant differences in either group. There were no significant variations in the median (IQR) values of neutrophil count (89 vs 91.25), WBC (15.65 vs 14.9), and NPAR (41.3 vs 43.7) between the two groups. Significant differences in albumin (3.330.521 vs. 3.10.51) were identified between the critical and non-critical groups. Conclusion: According to our research, the COVID-19 patients’ NPAR is a poor predictor of mortality. More study is still required to verify and elucidate the clinical implications of these findings. Keywords: Covid-19, Albumin, Neutrophil, Mortality, SARS